2021
DOI: 10.1016/j.ijid.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting epidemiology and genetic variation of Plasmodium vivax infecting Duffy-negative individuals across Africa

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 50 publications
8
41
2
Order By: Relevance
“…The last one gives rise to Duffy-negative phenotypes [ 9 , 10 ] and was thought to confer innate resistance to blood-stage infection with P. vivax and clinical malaria [ 11 ]. Recently, however, the widespread detection of P. vivax across individuals lacking Duffy antigen in many African countries [ 9 , 12 17 ] including Ethiopia [ 13 , 18 , 19 ] further complicates the current understanding of vivax malaria epidemiology in the region.…”
Section: Introductionmentioning
confidence: 99%
“…The last one gives rise to Duffy-negative phenotypes [ 9 , 10 ] and was thought to confer innate resistance to blood-stage infection with P. vivax and clinical malaria [ 11 ]. Recently, however, the widespread detection of P. vivax across individuals lacking Duffy antigen in many African countries [ 9 , 12 17 ] including Ethiopia [ 13 , 18 , 19 ] further complicates the current understanding of vivax malaria epidemiology in the region.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the highest prevalence of P. vivax infection among Duffy-negative individuals was identified in a Southern African study (Botswana, 86%, 95% CI 65%–95%) 27 , followed by Mid Africa (61%, 95% CI 6%–115%, I 2 = 99.59%, three studies 19 , 23 , 39 ), and North Africa (13%, 95% CI 9%–18%, I 2 = 100%, two studies 18 , 27 ). However, a low prevalence was reported in an East African study [6%, 95% CI 3%–9%, I 2 = 83.96%, five studies (six study areas) 25 , 27 , 29 , 41 , 43 ], followed by West Africa (4%, 95% CI 1%–8%, I 2 = 96.79%, two studies 24 , 42 ). But the lowest prevalence was reported in a South American study (Brazil, 1%, 95% CI 0%–2%, I 2 = 99.8%, two studies 20 , 21 ) (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Three studies 20 , 21 , 31 were conducted in South America (2/27, 7.4%) and Asia (1/27, 3.7%). Of the 24 African studies, six were conducted in East Africa (Ethiopia 28 , 43 , Madagascar 25 , 29 , Kenya 40 , and Ethiopia 41 ), seven in Mid Africa (Democratic Republic of Congo 19 , Cameroon 22 , 23 , 32 , 33 , 39 , Angola, and Equatorial Guinea 30 ), seven in West Africa (Mauritania 24 , 42 , Nigeria 36 , 37 , Senegal 34 , Mali 35 , and Benin 38 ), two in North Africa (Sudan 17 , 18 ), one in North and East Africa (Ethiopia and Sudan 26 ), and one in Ethiopia/Botswana/Sudan 27 . Twenty-two articles were cross-sectional studies (22/27, 81.5%), two were case-controls 12 , 40 , and one was a cohort study 35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations